FIQH DAN KONSTRUKSI PEMIKIRANNYA: UPAYA MENJAWAB ISU-ISU KONTEMPORER DI MASYARAKAT: FIQH DAN KONSTRUKSI PEMIKIRANNYA: UPAYA MENJAWAB ISU-ISU KONTEMPORER DI MASYARAKAT - karmawan karmawan (ISLAMIKA, 2023)
Abstract This research discusses the crucial role of fiqh in dealing with contemporary issues faced by Islamic society. Fiqh, as the main branch of Islamic science, not only establishes religious laws, but also presents an adaptive conceptual framework to respond to the dynamics of the modern era. The construction of fiqh thought includes the ability to carry out ijtihad and contemporary interpretation, provide ethical and moral views in dealing with social issues, and stimulate dialogue between religions and cultures. This article details how fiqh and its thought constructs are able to provide a solid foundation for Muslim society in responding to challenges and changes in today's society. With its emphasis on justice, balance, and education, fiqh is an important instrument in forming deep understanding, providing moral direction, and supporting social harmony amidst the complexity of contemporary reality. Keywords: Fiqh, construction of thought, contemporary issues, society